2020
DOI: 10.32539/jkk.v7i1.9657
|View full text |Cite
|
Sign up to set email alerts
|

A Review : Plasmodium knowlesi

Abstract: Malaria adalah suatu penyakit yang disebabkan oleh parasit yang termasuk dalam anggota spesies dari genus Plasmodium. Plasmodium knowlesi adalah parasit malaria yang ditemukan pada kera ekor-panjang dan ditemukan pertama kali pada tahun 1930 pada spesimen Macaca fascicularis dari Singapura. Pada tahun 2004 dilaporkan terjadi infeksi P. knowlesi pada manusia di Sarawak, Borneo Malaysia dan penemuan ini menjadikan P. knowlesi sebagai spesies parasit malaria kelima yang menginfeksi manusia. Plasmodium knowlesi da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Several studies have reported that not only established in Malaysia but also, Plasmodium knowlesi transmission has spread to other parts of Southeast Asia such as Thailand [16], Cambodia [17], Myanmar [18], Singapore [19], Indonesia [9], Vietnam [20], and the Philippines. This current situation causes Plasmodium knowlesi, the fifth Plasmodium species that can infect humans besides Plasmodium falciparum, Plasmodium malariae, Plasmodium vivax, and Plasmodium ovale [4,5].…”
Section: Zoonotic Malaria: Brief History and Current Situationmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported that not only established in Malaysia but also, Plasmodium knowlesi transmission has spread to other parts of Southeast Asia such as Thailand [16], Cambodia [17], Myanmar [18], Singapore [19], Indonesia [9], Vietnam [20], and the Philippines. This current situation causes Plasmodium knowlesi, the fifth Plasmodium species that can infect humans besides Plasmodium falciparum, Plasmodium malariae, Plasmodium vivax, and Plasmodium ovale [4,5].…”
Section: Zoonotic Malaria: Brief History and Current Situationmentioning
confidence: 99%
“…Plasmodium knowlesi is transmitted to vectors with the help of Anopheles mosquitoes, such as Anopheles latens (Sarawak), Anopheles balabacencis (Sabah), Anopheles cracens (Peninsular Malaysia), and Anopheles leucosphyrus (Indonesia). The natural hosts of Plasmodium knowlesi are Macaca nemestrina, Macaca fascicularis, and P. melalophus [3,4,5].…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations